Evaluation the Filter of Agricultural Drainage of Sitkheres Researches Station-Lattakia - يزبك, إبراهيم (Latakia University Journal -Engineering Sciences Series, 2020)
Food security has become an urgent need that every society seeks to achieve, but this can only be achieved through the optimal use of agricultural land, the prevention of soil salinity, and the establishment of irrigation and drainage projects on the basis of correct scientific data. The careful selection of the buried drain filter changes the specifications of water flow near the sinks, ensures even water entry into the water-receiving holes and reduces entry resistance. The purpose of the research is to study and evaluate the filter of the buried drainage in the irrigation research station in Sitkheres -Lattakia, where the field survey of the research area found problems in the operation of drainage pipes caused by sediments inside the drainage pipes, due to the inaccuracy in the study of the filter used in terms of the type of filter and its design. After conducting the field and laboratory studies required to determine the appropriate drainage filter, it was found that the coarse and soft sea pebbles and olive argoon meet the three conditions required in the selected material as a filter in the drainage networks of the studied area. The study recommends that the drainage pipe system should be maintained by washing it under pressure.